Substrates and physiological functions of secretase rhomboids proteases - Freeman, M; Lastun, V; Grieve, A (Elsevier, 2016)
Rhomboids are conserved intramembrane serine proteases with widespread functions. They were the earliest discovered members of the wider rhomboid-like superfamily of proteases and pseudoproteases. The secretase class of rhomboid proteases, distributed through the secretory pathway, are the most numerous in eukaryotes, but our knowledge of them is limited. Here we aim to summarise all that has been published on secretase rhomboids in a concise encyclopaedia of the enzymes, their substrates, and their biological roles. We also discuss emerging themes of how these important enzymes are regulated.